The Impact of Behavioral Accounting on Accounting Decision-Making A Field Study in Algerian Institutions - mohamed esedik, Elfodil (Journal of Ecohumanism, 2026)
The aim of this study was to analyze the effect of behavioral accounting on the accounting decision-making process within a group of Algerian institutions, by focusing on the psychological and organizational factors that may influence the professional judgment of the accountant. The study is based on the hypothesis that accounting decisions do not rely solely on technical standards and rules but are also affected by cognitive biases, professional pressures, and the organizational culture prevailing in the work environment. The study adopted a descriptive-analytical approach, and data were collected using a questionnaire directed at a sample of accountants and financial managers in several Algerian institutions. The data were statistically analyzed to test the nature of the relationship between the dimensions of behavioral accounting and the quality of the accounting decisions made. This study seeks to highlight the importance of the behavioral dimension in accounting practice and to contribute to expanding research in this field within the Algerian context, while providing recommendations that support the development of professional performance and enhance the objectivity of accounting decisions.